Household food insecurity is associated with a higher burden of obesity and risk of dietary inadequacies among mothers in Beirut, Lebanon - Lamis Jomaa; Farah Naja; Ruba Cheaib; Nahla Hwalla (BMC, 2017)
Abstract Background Mixed evidence exists with respect to the association between household food insecurity (HFIS) and obesity in low-to-middle income countries (LMICs), particularly among women. This study aimed to measure socioeconomic correlates of HFIS and explores its association with dietary intake and odds of obesity among mothers in Lebanon, a middle-income country undergoing nutrition transition. Methods A cross-sectional study was conducted among a representative sample of households (n = 378) in Beirut, Lebanon. Surveys were completed with mothers of children <18 years. HFIS was measured using a locally-validated, Arabic-translated Household Food Insecurity Access Scale (HFIAS). Dietary intake was assessed using the multiple pass 24-h recall method. Associations between HFIS (food vs food insecure) and socio-demographic characteristics were reported using crude and adjusted odds ratios. The odds of consuming <2/3rd Dietary Reference Intakes (DRIs) for nutrients among mothers from food secure and food insecure households were explored. In addition, logistic regression analyses were conducted to explore the association of HFIS with obesity (BMI ≥ 30 kg/m2) and at-risk waist circumference (WC ≥ 80 cm) among mothers. Results HFIS was found among 50% of study sample and was inversely associated with household income and mother's educational level, even after adjusting for other socioeconomic variables (p < 0.01). Mothers in food insecure households reported consuming significantly less dairy products, fruits, and nuts yet more breads and sweets; and they had higher odds of consuming <2/3rd the DRI's for key micronutrients (potassium, folate, and vitamin C) compared to secure ones. Adjusting for socioeconomic correlates, food insecure mothers had 1.73 odds of obesity (95% CI: 1.02-2.92) compared to food secure mothers. Conclusions High HFIS prevalence was reported among urban Lebanese households. Mothers from food insecure households had a high risk of dietary inadequacy and obesity. Adequate evidence-based public health strategies are needed to reduce the vulnerability of mothers to food insecurity in LMIC settings and alleviate their risk of a high burden of nutrient insecurity and obesity.